Purification and Characterization of Membrane-Bound Polyphenol Oxidases and Peroxidases from Metroxylon Sagu Rottb - Hassan Onsa, Galila (2003)
The histochemical studies indicated that Metroxylon sagu polyphenol oxidases (mPPO: E.C.1.10.3.2) and peroxidase (mPOD: E.C.1.11.1.7) were cellular membrane-bound enzyme. The enzymes were isolated using temperature-induced phase partitioning technique with Triton X-114. The temperature-induced phase partitioning extract was subsequently chromatographed on DEAE-Toyopearl 650M, Butyl-Toyopearl 650 M and Sephadex G-100. Two mPPO isoenzymes designated as mPPO-I and mPPO-II were purified 43.9 and 76.1-fold respectively. On Native- PAGE, both isoenzymes were resolved into two charge isomers, very close in charge density. The molecular masses of mPPO-I and mPPO-II were 38 and 39 kDa respectively. The latency that was observed for the temperature-induced phase partitioning mPPO extract was not detected in purified enzyme and a fully active mPPO was obtained. The optimum pHs of mPPO-I and mPPO-II were 4.5 and 5.0 respectively. mPPO isoenzymes did not react with monophenols but were highly reactive toward diphenols and triphenols at varying affinities. Ascorbic acid with K, value of 0.015 mM was the most potent inhibitor for mPPO followed by sodium metabisulfite, L-cysteine, kojic acid, and p-coumaric acid. Metal ions tested affected both isoenzymes similarly. The enzyme activity was enhanced in the presence of 1.0 mM Cu2+ and hardly affected by 10 mM Ca2+, Ae+, Ni2+ and Hg2+. mPPO-II showed high thermal stability with activation energy of heat inactivation (Ea) of 40.34 compared to 32.94 kcal.mol⁻¹ for mPPO-I. mPODs were weakly adsorbed onto DEAE-Toyopearl 650M. The eluent was subsequently chromatographed onto CM-Toyopearl 650M followed by Sephadex G-100. Two isoenzymes; mPOD-I and mPOD-U were purified 76.5- and 37.0-fold respectively. Their molecular masses were of 51.2 and 43.8 kDa respectively. mPOD-I and mPOD-II had an optimum pH at 6.0 and 5.5 respectively. Both mPOD isoenzymes showed high efficiency of interaction with TMBZ, guaiacol, diphenols and triphenols only in the presence of H202. Ascorbic acid was the most potent inhibitor of mPOD with Ki value of 0.01 mM, followed by sodium metabisulfite, Lcysteine and p-coumaric acid. mPOD-I activity was enhanced in the presence of 1.0 mM Ae+, Ca2+, Fe3+, Ni2+ better than mPOD-II and both isoenzymes were not affected by Hg2+ and Cu2+ and moderately inhibited by the presence of 10 mM Zn2+ and Co2+. mPOD-I was more thermal stable with an inactivation energy (Ea) of 45.77 kcal.mol⁻¹ compared to 40.62 kcal.mol⁻¹for mPOD-II. Other thermodynamic parameters such as enthalpy and entropy were also determined and compared.